Confining stress path dependent stress-strain model for pre-tensioned steel-confined concrete. (15th December 2019) - Chin, Chee-Loong; Ma, Chau-Khun; Awang, Abdullah Zawawi; Tan, Jia-Yang; Ong, Chin-Boon; Omar, Wahid
Highlights: Pre-tensioning activates confining effect earlier and improves confinement efficiency. The influence of confining stress path can be accumulated and dissipated. Pre-tensioning decreases the influence of confining stress path on steel-confined concrete. An expression is used to quantify the effect of confining stress path on confined concrete. Abstract: Stress-strain model of a confined concrete is one of the most important factors to predict the structural behaviour of confined reinforced concrete elements. Previous research has revealed that axial stress of confined concrete is always less than that in comparison with actively confined concrete due to confining stress path dependency. In view of this, this paper presents an investigation the influence of confining stress path on the stress-strain behaviour of pre-tensioned steel-confined concrete. It is shown that the variation in pre-tension level influences the confining stress path and hence the stress-strain behaviour. An expression is proposed to cater for such confining stress path dependency based on a proposed concept of accumulation and dissipation of confining stress path effect. By incorporating this into existing framework of analysis-oriented model, a stress-strain model based on incremental procedure is proposed. It is demonstrated that the model is capable of capturing the different stress-strain behaviour due to different of pre-tension level. The accuracy of the model is assessed by using an experimental database at the last part of this paper.